CM-SegNet: A deep learning-based automatic segmentation approach for medical images by combining convolution and multilayer perceptron. (August 2022) - Xing, Wenyu; Zhu, Zhibin; Hou, Dongni; Yue, Yaoting; Dai, Fei; Li, Yifang; Tong, Lin; Song, Yuanlin; Ta, Dean
Abstract: Accurate segmentation of lesions in medical images is of great significance for clinical diagnosis and evaluation. The low contrast between lesions and surrounding tissues increases the difficulty of automatic segmentation, while the efficiency of manual segmentation is low. In order to increase the generalization performance of segmentation model, we proposed a deep learning-based automatic segmentation model called CM-SegNet for segmenting medical images of different modalities. It was designed according to the multiscale input and encoding-decoding thoughts, and composed of multilayer perceptron and convolution modules. This model achieved communication of different channels and different spatial locations of each patch, and considers the edge related feature information between adjacent patches. Thus, it could fully extract global and local image information for the segmentation task. Meanwhile, this model met the effective segmentation of different structural lesion regions in different slices of three-dimensional medical images. In this experiment, the proposed CM-SegNet was trained, validated, and tested using six medical image datasets of different modalities and 5-fold cross validation method. The results showed that the CM-SegNet model had better segmentation performance and shorter training time for different medical images than the previous methods, suggesting it is faster and more accurate in automatic segmentation and has great potential application in clinic. Highlights: A deep learning-based CM-SegNet model was designed for segmenting medical images. The model realizes the feature analysis by combining MLP and convolution modules. The model can obtain better segmentation accuracy with higher efficiency.